Does afforestation deteriorate haze pollution in Beijing–Tianjin–Hebei (BTH), China? - X. Long; X. Long; N. Bei; J. Wu; X. Li; T. Feng; L. Xing; S. Zhao; J. Cao; X. Tie; X. Tie; Z. An; et al. (Atmospheric Chemistry and Physics, 2018)
Although aggressive emission control strategies have been implemented recently in the Beijing–Tianjin–Hebei area (BTH), China, pervasive and persistent haze still frequently engulfs the region during wintertime. Afforestation in BTH, primarily concentrated in the Taihang and Yan Mountains, has constituted one of the controversial factors exacerbating the haze pollution due to its slowdown of the surface wind speed. We report here an increasing trend of forest cover in BTH during 2001–2013 based on long-term satellite measurements and the impact of the afforestation on the fine-particle (PM2.5) level. Simulations using the Weather Research and Forecast model with chemistry reveal that afforestation in BTH since 2001 has generally been deteriorating the haze pollution in BTH to some degree, enhancing PM2.5 concentrations by up to 6 % on average. Complete afforestation or deforestation in the Taihang and Yan Mountains would increase or decrease the PM2.5 level within 15 % in BTH. Our model results also suggest that implementing a large ventilation corridor system would not be effective or beneficial to mitigate the haze pollution in Beijing.